Skin flap thickness and magnet strength in Cochlear implants. (4th March 2021) - Searle, Tamara; Marshall, Evie; Craddock, Louise; Monksfield, Peter
Abstract : Objectives: The new CI600 series cochlear implants (Nucleus ® Profile™ Plus Series; CI) are more MRI (magnetic resonance imaging) compatible. The magnet's attraction force is lower, possibly posing a problem in patients needing a higher strength magnet due to increased skin thickness. This study aims to investigate the relationship between skin thickness and magnet strength in patients undergoing cochlear implantation. Methods: This cross-sectional study used data from 46 patients with cochlear implants. Data collected included age, body mass index, magnet strength used, pre-operative and post-operative imaging and skin thickness. Results: There was a weak, positive correlation between magnet strength and skin thickness, which was not statistically significant ( r (46) = 0.149, p  = 0.324). There was a weak, positive correlation between magnet strength and body mass index, which was not statistically significant ( r (46) = 0.113, p  = 0.456). There was a moderate, positive correlation between body mass index and skin thickness, which was statistically significant ( r (46) = 0.362, p  = 0.012). Discussion: The increased skin thickness in patients with higher body mass indexes, might mean that these patients will require a stronger magnet. Conclusion: There are concerns that the lower attraction force in the CI600 (Nucleus ® Profile™ Plus Series) may pose a retention problem for these patients. This might mean that discussions about skin flap reduction surgery are needed.